Board characteristics and real performance in Malaysian state-owned enterprises (SOEs) - Mohammed Shawtari, Fekri Ali; Mohamad, Muslim Har Sani; Abdul Rashid, Hafiz Majdi; Moh’d Ayedh, Abdullah (Emerald Group Publishing Ltd., 2017)
Purpose